Investigation of Integrated Marketing Communications to the Buyer in the Retail Trade Network (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Overview scientific approaches to the specific functioning of integrated marketing communications at point of sale; described five major influence over buyers in the retail trade network; results of research and analyzes the effectiveness of the impact of integrated marketing communications in the retail trade network shoes «Chobitok».
Keywords: integrated marketing communications, retail trade network indicator RMI, efficiency IMC